The Legal Politics of State Defense in the Concept of Sovereignty of the Unitary State of the Republic of Indonesia - Wahyu Mujiono (Journal of Social Research, 2023)
State defense is any effort to maintain state sovereignty, the territorial integrity of the Unitary State of the Republic of Indonesia, and the safety of the entire nation from threats and disturbances to the integrity of the nation and state. The goal to be achieved is to find and analyze state defense arrangements in the concept of Sovereignty of the Unitary State of the Republic of Indonesia. and to find and analyze the ideal concept of state defense legal politics in the concept of Sovereignty of the Unitary State of the Republic of Indonesia. This research uses normative juridical research with statutory, conceptual, comparative, philosophical, and historical approaches. Sources of legal materials used primary, secondary and tertiary sources of legal materials, the analysis used is qualitative. Based on the results of the study, it shows that state defense arrangements are regulated in Article 1 of Law number 3 of 2002 concerning State Defense and Law Number 34 of 2004 concerning the TNI in this Law, what is meant by state defense is all efforts to maintain state sovereignty, the territorial integrity of the Unitary State of the Republic of Indonesia, and the safety of the entire nation from threats and disturbances to the integrity of the nation and state. The Ideal Concept of State Defense Legal Politics in the Concept of Sovereignty of the Unitary State of the Republic of Indonesia is Defense Law Politics which refers to various juridical policies, where elements of the people must be given proportional space in defense considering the dynamics of the development of an increasingly dynamic national, regional and global strategic environment.